(3TQM GdLeds - (3CHhYHO Gddg eMeO Hf YeQ Hf jhSa, GHf GdaNGQs; (3GdRLGLj , CHh GdbGSe,J (B337 (3g` s ((3GdLGeY GdcHjQ HZQfGWI s)
(3ChdgG (B:s
(3gPG eG CedGg YdjfG SjOfG GdeYQha HGHf GdaNGQ CedGg YdjfG HGdLGeY GdcHjQ HZQfGWI EYQGHg, abGd bhe(B: s
(3BNQgG (B:s
(3hGdEYdGd HgeRI Odjd hKjb Ydi GYJHGQg HaYd eYJd GdYjf, hdeG cGf Ydi GdfUH dUM EP dG jYJHQ Hg aYd hGddg CYde GfJgi eG bjO ddTjN s
(3CedGg GdeDdas
(3hHg CKQ JbWjYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B124s
Keywords: (3GdfMhs